Síntese e avaliação anti-SARS-CoV-2 e fotofísica dos 1,10- fenantrolina-4,5-imidazo-benzocalcogenazóis - Sarturi, Joelma Menegazzi (2022)
In this work, a new serie of 1,10-phenanthroline-4,5-imidazo-benzochalcogenazoles 5a-h/ 6a-g obtained through the Debus-Radziszeski condensation was synthesized. Benzoxazoles and benzothiazoles were previously synthesized and derivatives 1,10- phenanthroline-4,5-imidazo-benzochalcogenazoles 5a-h/ 6a-g were obtained with yields ranging from 43 to 85%. The photophysical properties of compounds 5a-h/ 6a-g were evaluated against UV-Vis absorption, fluorescence emission and quantum yield fluorescence. Regarding the absorption spectrum of the derivatives, they had their spectra reported in the ultravioleta region and the fluorescence emission the compounds was observed in the purple to blue region. The quantum yield fluorescence (Φf) ranged from 0,10 – 0,71. The analyses of the biological activity about derivatives were carried out in silico, through molecular anchorage and in live, against the protease MPRO of the SARS-CoV-2 virus, which causes the disease COVID 19. The results of molecular anchorage demonstrate high affinity of the derivatives with the active place of the protease M. Additionally, the activity of these compounds as inhibitors of SARS-CoV2 was evaluated in vitro, and the compunds showed a very significant viral inhibition rate, with EC50 of 0,17 – 0,19 µM.